The relevance of Eastern Canadian native willows as alternatives to Salix miyabeana in nitrogen leachate-treating vegetative filters - Auger, Camille; Labrecque, Michel; Susini, Caroline; Laur, Joan (Frontiers in Environmental Science, 2025)
As waste from engineered landfills decomposes, it produces nitrogen (N)-laden leachate that cannot be directly released into the environment. Plants such as willows have the potential to phytofilter this polluted water but must be able to tolerate large loads of contaminants and flooding conditions. To date, however, it is mainly exotic species that have been used in for the treatment of leachates in a pilot project conducted on a technical landfill. It would be useful to compare the effectiveness of native species from eastern Canada with that of the Salix miyabeana ‘SX64’, a willow cultivar used in the pilot project. Three willows indigenous to Canada: S. amygdaloides, S. bebbiana and S. nigra, were tested alongside S. miyabeana. A mesocosm experiment was conducted under semi-controlled conditions over six weeks to document the impact of various nitrogen overfertilization and flooding treatments on plant development, and to test the plants’ tolerance to these constraints to evaluate their suitability for large-scale vegetative filters. Overall, growth and biomass production of S. nigra and S. amygdaloides were not affected by the treatments. Furthermore, S. nigra was ten times more efficient than the cultivar of S. miyabeana in terms of decontamination capacity. While still in the juvenile phase, S. nigra plants removed the equivalent of 240m3 per hectare of the N-contaminated water initially applied (60 kg of N), under both permanent and cyclic flooding. These results suggest that native species could be given greater in future projects.